Problems of Arabic Language Learning in Class VII of SMP IT Al-Hijrah: Causal Factors and Solution Strategies - Ardea Pramesti; Tri Lasti; Ade Dwi Juliani; Sahkholid Nasution (Jurnal Multidisiplin Sahombu, 2024)
The Arabic language , with its rich grammatical structure , is often considered difficult by most students who learn it . In addition , several others factors make Arabic even harder to learn , whether from the environment , learning methods , or even from the students themselves . This is the issue face by seventh grade students at SMP IT Al-Hijrah in learning Arabic . This research uses a qualitative approach where the researcher presents data in descriptive form ( written ) rather than numerical figures . Data collection was conducted through observation , documentation , and in- depth interviews related to information about the subjects and objects of the research , focus on the issues of learning Arabic in the seventh grade at SMP IT Al-Hijrah. The research findings indicate that the learning problems in the seventh grade at Al-Hijrah IT Middle School stem from factors such as students ' lack of abilities to read the Qur'an , which is closely related to the Arabic language , students ' educational background , insufficient class hours , lack of learning media, and the school environment that is not fully supportive . The efforts made by the teacher to address these learning issues include collaboration between Arabic language teachers and memorization teachers to synchronize students ' Quran reading skills with their Arabic learning , changing teaching strategies by grouping students based on their educational background , constantly motivating students , and striving to create an Arabic speaking environment in the school , starting with the teachers at SMP IT Al-Hijr Top of the Form ah.